PSYCHIATRIC MORBIDITY AMONG ADOLESCENT STUDENTS WITH DEAFNESS IN A NIGERIAN SCHOOL FOR PERSONS WITH SPECIAL NEEDS - O., Ogundiran; B. A., Eegunranti; A. C., Ogundiran; J., Falade; Olaosun, Adedayo Olugbenga (Advances in Social Sciences Research Journal, 2018)
Adolescence is a transitional period from the age of 10 to 19 years, when young people undergo physical, biological, psychological, cognitive, social and economic changes. Adolescence could be a challenging period for people. Adolescents with deafness face greater challenges as their communication skills and access to information relevant to their social life is limited. This study is a cross-sectional school–based one conducted among 105 adolescent students with deafness at Osun State Secondary School for Persons with Special Needs, Osogbo, Nigeria. Otoscopy was performed on all the participants to check for those with cerumen impaction and other middle ear pathologies. Pure Tone Audiometry was done by a certified Audiologist to determine the hearing thresholds of all the participants. General Health Questionnaire (GHQ 12) was used to determine the prevalence of psychiatric morbidity among the participants. The majority of the participants were late adolescents 96.2% (15 – 19 years), with a mean age of 17.45 years (SD = 1.50).There were 60 male and 45 female adolescent students with deafness that participated in the study .76.2 % were normal (negative psychiatric morbidity) while almost a quarter (23.8%) of the respondents had positive psychiatric morbidity. Adolescent student with deafness are at risk of psychiatric morbidity. Prompt provision of effective communication within the family and societal support will go a long way to preventing many of these problems. Adolescence is a transitional period from the age of 10 to 19 years, when young people undergo physical, biological, psychological, cognitive, social and economic changes. Adolescence could be a challenging period for people. Adolescents with deafness face greater challenges as their communication skills and access to information relevant to their social life is limited. This study is a cross-sectional school–based one conducted among 105 adolescent students with deafness at Osun State Secondary School for Persons with Special Needs, Osogbo, Nigeria. Otoscopy was performed on all the participants to check for those with cerumen impaction and other middle ear pathologies. Pure Tone Audiometry was done by a certified Audiologist to determine the hearing thresholds of all the participants. General Health Questionnaire (GHQ 12) was used to determine the prevalence of psychiatric morbidity among the participants. The majority of the participants were late adolescents 96.2% (15 – 19 years), with a mean age of 17.45 years (SD = 1.50).There were 60 male and 45 female adolescent students with deafness that participated in the study .76.2 % were normal (negative psychiatric morbidity) while almost a quarter (23.8%) of the respondents had positive psychiatric morbidity. Adolescent student with deafness are at risk of psychiatric morbidity. Prompt provision of effective communication within the family and societal support will go a long way to preventing many of these problems.